Overview of catalysts in biodiesel production - Talha, Nur Syakirah; Sulaiman, Sarina (ARPN, 2016)
Transesterification is one of the methods for biodiesel production in which oil or fat is reacted with alcohol, such as methanol or ethanol, in the presence of a catalyst to form alkyl ester and glycerol. The cost of biodiesel production is mainly affected by the system used and cost of feedstock. Currently, waste oil or fat is used in the production of biodiesel as 70 to 90% of the production cost is attributed to raw materials. Alternatively, overall cost of production can also be reduced by optimizing the efficiency of catalyst used. Therefore, this review paper is aimed to give an overview on the recent trends of catalyzed transesterification and the advantages and disadvantages of heterogeneous acid/base, homogeneous acid/base, and enzymatic transesterification. Heterogeneous base catalyst is commonly used because of its reusability, easier to separate from product, higher reaction rate, lower cost, and require less energy as compared to acidcatalyzed transesterification. However, heterogeneous base catalyst still suffers with the limitations of diffusion, possibility of saponification to occur, sensitive to FFA content and produce more wastewater. With intense research focus and development, an ideal catalyst can indeed be develop for optimum production of biodiesel that economically feasible and environmentally benign for a better future.